The search for corporate strategic credibility concepts and cases in global strategy communications - Higgins, Richard B.
Dr. Higgins makes clear that "corporate strategy, regardless of how elegantly conceived, how comprehensive its scope or how forward-looking its thrust, does not provide competitive advantage until it is communicated, understood, values, and acted upon by a variety of key corporate strategy communications. With two chapters devoted to conceptual foundations and empirical research, plus five new case studies illustrating his points, Dr. Higgins's book not only builds on existing research in strategic planning and management and "reputation management," but offers new research findings as well. Interdisciplinary, integrative, and international in scope, the book will be of special interest to corporate management, strategic planners, corporate communications and investor relations executives, and other professionals in the investment community, and to academics with similar research and teaching interests.